Stimulating Parenting Practices in Indigenous and Non-Indigenous Mexican Communities - Heather A. Knauer (International Journal of Environmental Research and Public Health, 2017)
Parenting may be influenced by ethnicity; marginalization; education; and poverty. A critical but unexamined question is how these factors may interact to compromise or support parenting practices in ethnic minority communities. This analysis examined associations between mothers’ stimulating parenting practices and a range of child-level (age; sex; and cognitive and socio-emotional development); household-level (indigenous ethnicity; poverty; and parental education); and community-level (economic marginalization and majority indigenous population) variables among 1893 children ages 4–18 months in poor; rural communities in Mexico. We also explored modifiers of associations between living in an indigenous community and parenting. Key findings were that stimulating parenting was negatively associated with living in an indigenous community or family self-identification as indigenous (β = −4.25; SE (Standard Error) = 0.98; β = −1.58; SE = 0.83 respectively). However; living in an indigenous community was associated with significantly more stimulating parenting among indigenous families than living in a non-indigenous community (β = 2.96; SE = 1.25). Maternal education was positively associated with stimulating parenting only in indigenous communities; and household crowding was negatively associated with stimulating parenting only in non-indigenous communities. Mothers’ parenting practices were not associated with child sex; father’s residential status; education; or community marginalization. Our findings demonstrate that despite greater community marginalization; living in an indigenous community is protective for stimulating parenting practices of indigenous mothers.